2017
DOI: 10.1002/syn.21968
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of norepinephrine α1 receptor blockade on dopamine levels: A pilot PET study with [11C]‐(+)‐PHNO in controls

Abstract: Interest in a role for norepinephrine (NE) in substance use disorders has increased over recent years. In particular, its interaction with dopamine (DA) is of importance. In this study, positron emission tomography (PET) was used to explore the impact of prazosin (an alpha 1 NE antagonist) on DA levels. Healthy volunteers were administered prazosin for approximately 4 weeks at the daily dose of 15 mg to reach steady state. Participants were scanned with PET imaging and the [ C]-(+)-PHNO tracer at baseline (bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Another limitation is that the relatively high affinity of [ 11 C] FLB457 for dopamine D 2 /D 3 receptors does not permit reliable measurements of binding (ie, does not achieve equilibrium during the scan duration) in the striatum, a region that is commonly studied in addiction research as part of the mesolimbic dopamine system. A recently published study found that healthy nonsmokers who underwent treatment with prazosin, an alpha 1 adrenergic antagonist, had increased [ 11 C]PHNO (D 3 receptor agonist) binding in the dorsal caudate from baseline, indicative of a decrease in dopamine levels (Le Foll et al, 2017). Guanfacine and prazosin act through different mechanisms (ie, alpha 2a agonist and alpha 1 antagonist, respectively) to restore the balance of norepinephrine and dopamine levels, and both have been studied for the treatment of stress related disorders .…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that the relatively high affinity of [ 11 C] FLB457 for dopamine D 2 /D 3 receptors does not permit reliable measurements of binding (ie, does not achieve equilibrium during the scan duration) in the striatum, a region that is commonly studied in addiction research as part of the mesolimbic dopamine system. A recently published study found that healthy nonsmokers who underwent treatment with prazosin, an alpha 1 adrenergic antagonist, had increased [ 11 C]PHNO (D 3 receptor agonist) binding in the dorsal caudate from baseline, indicative of a decrease in dopamine levels (Le Foll et al, 2017). Guanfacine and prazosin act through different mechanisms (ie, alpha 2a agonist and alpha 1 antagonist, respectively) to restore the balance of norepinephrine and dopamine levels, and both have been studied for the treatment of stress related disorders .…”
Section: Discussionmentioning
confidence: 99%